Development of Chemistry E-Modules Based on Problem Based Learning (PBL) on Colloidal Material at SMAN 2 Muaro Jambi: Penelitian - Adriyan Wijaya Putra; Harizon; Haryanto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Education is one of the benchmarks of a nation's progress. A nation can be said to be advanced, one of which is if education within the nation is advanced. Along with the development of globalization and science and technology, education continues to progress in accordance with the times. In the context of education, the main goal is to produce individuals who not only possess knowledge, but also strong critical thinking skills. Chemistry education in high school often faces challenges in conveying abstract materials such as colloids to students during learning activities. This study aims to develop an e-module for colloid material based on Problem Based Learning (PBL) to help students understand abstract materials such as colloids. This has been proven through several previous studies that developed e-modules on several other abstract materials and proved effective. Therefore, this e-module has the potential to help students understand colloid material.